2012
DOI: 10.1177/1741143212438217
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Transformational Leadership and Organizational Commitment

Abstract: The purpose of this article is to determine the relationship between transformational leadership of vocational school principals on vocational teachers’ organizational commitment. A random sample of 340 vocational teachers responded to a three-part instrument (the transformational leadership questionnaire, the organizational commitment questionnaire and a demographic section). Means, standard deviations, Pearson correlations and stepwise regression analysis were used to analyse the data. The findings indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 36 publications
(35 reference statements)
2
43
1
6
Order By: Relevance
“…Since the 1980s, there has been significant growth in the number of studies about the model of transformational leadership that constructed vision‐building, intellectual stimulation and individual consideration as the main characteristics of leaders in successful organisations (Kouzes & Posner, ). In education, two decades later, a new conceptualisation of leadership in terms of moral leadership that elucidates some reference to transformational leadership and to moral and social justice issues as equality, discrimination, equity and class, emerged (Lindsey & Lindsey, ; Khasawneh et al., ). While most of the research on these dimensions has been conducted in Western countries, we found nine papers that examined transformational leadership or moral aspects of leadership, explicitly and implicitly, in Arab countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1980s, there has been significant growth in the number of studies about the model of transformational leadership that constructed vision‐building, intellectual stimulation and individual consideration as the main characteristics of leaders in successful organisations (Kouzes & Posner, ). In education, two decades later, a new conceptualisation of leadership in terms of moral leadership that elucidates some reference to transformational leadership and to moral and social justice issues as equality, discrimination, equity and class, emerged (Lindsey & Lindsey, ; Khasawneh et al., ). While most of the research on these dimensions has been conducted in Western countries, we found nine papers that examined transformational leadership or moral aspects of leadership, explicitly and implicitly, in Arab countries.…”
Section: Resultsmentioning
confidence: 99%
“…'political', 'cultural', 'transformational', 'moral' and 'instructional') have been conceptualised to propose the 'right' leadership style and the desirable leader-follower relations in educational organisations (Stoll & Temperley, 2009;Furman, 2012). Likewise, collaborative, developmental and transformational approaches to EDLM have been widely advanced in many educational systems, based on principles of equality and equity (Fletcher, Greenwood, Grimley & Parkhill, 2011;Lindsey & Lindsey, 2011;Khasawneh, Al-Omari & Abu-Tineh, 2012;Yang, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Teacher organizational commitment has been studied thoroughly throughout the years because of its effect on a number of significant organizational outputs, such as intention to leave and absenteeism (negative effect), retention, performance and person-organization fit (positive effect) (e.g. Khasawneh, Omari & Abu-Tineh, 2012;Nir, 2002;Sezgin, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the views that the organizational commitment perception, which is related to the employees seeing themselves as a permanent member of the organization and showing the attitudes that integrate them with the organization, is affected by leadership behaviors (Meyer & Allen, 1991;Mowday, Porter, & Steers, 1982;Wiener, 1982) and the results of many studies also imply large positive effect of educational leadership on organizational commitment (Avolio, Zhu, Koh, & Bhatia, 2004;Dunn, Dastoor, & Sims, 2012;Howell & Hall-Merenda, 1999;Hulpia, Devos, & Keer, 2011;Jackson, Meyer, & Wang, 2013;Kirkpatrick & Locke, 1996;Khasawneh, Omari, & Abu-Tineh, 2012;Leithwood & Sun, 2012;Lok & Crawford, 2004;Thamrin, 2012). One of the important findings of this study is the direction and strength of the effect of educational leadership on organizational commitment.…”
Section: Discussion About Findings Between Educational Leadership Andmentioning
confidence: 99%
“…It is possible to find researches measuring the relationship between educational leadership and organizational commitment perceived by teachers (Avolio, Zhu, Koh, & Bhatia, 2004;Dunn, Dastoor, & Sims, 2012;Howell & Hall-Merenda, 1999;Hulpia, Devos, & Keer, 2011;Jackson, Meyer, & Wang, 2013;Kirkpatrick & Locke, 1996;Khasawneh, Omari, & Abu-Tineh, 2012;Leithwood & Sun, 2012;Lok & Crawford, 2004;Thamrin, 2012). Researchers often believe that there is a relationship between the behaviors of school administrators and teachers' organizational commitment.…”
Section: Educational Leadership and Organizational Commitmentmentioning
confidence: 99%